Synthesis OF Ligands O.F BIS-Oxadiazole Triazole Witb Open OR Close Sides and Their Complxes With (Ctlf, Pdll) - - Me.hdi, W.K.; Musa, F. H.; Fadhel, H. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A  OUI,tiper  of LWW lig_;:tnds  .of  ppen sides. of Bis-'Oxad1azoJeÂ· andÂ·Bis-triazole   derived from dichloroetbane  and  [Bis  0-ohloro   et!:ty)= :=::                                                 =ether)] (BCEE)' wersynthesi:zed. These inelude: 1, 4- bis[-3{thio- 2 - . (ChloroÂ·ethyl)l1 1;4 - oxadiazole ......$yl] butane (-L I);1  4 B'is {phenl-3{thio - 2 ( 2 -chloroethoxy)- ethyl} 1 3A- oxadiazole-5yl)  butane (t2)'l His [4-_ph nyl -3{thio(chloro thy:l)}1; ,4 - ttiazoJ Syl]  methane (L1) Bis[ phehyl-3{, thi-0- 2( 2-chloroethoxy) ethyl}  1,,2:,4- triazole- 5yl]: =methane  (L:4)    1,. 2- bi[